Resurgence of Measles in Europe: A Systematic Review on Parental Attitudes and Beliefs of Measles Vaccine - Annika B. Wilder-Smith; Kaveri Qureshi (Springer, 2019)
Background and Objectives: Europe has experienced a major resurgence of measles in recent years, despite the availability and free access to a safe, effective, and affordable vaccination measles, mumps and rubella vaccine (MMR). The main driver for this is suboptimal vaccine coverage. The three objectives of this study are to synthesize and critically assess parental attitudes and beliefs toward MMR uptake, to develop strategies and policy recommendations to effectively improve MMR vaccine uptake accordingly, and ultimately to identify areas for further research. Methods: A systematic review was conducted using primary studies from PubMed, Medline, Embase, and Scopus published between 2011 and April 2019. Inclusion criteria comprised primary studies in English conducted in Europe and studying parental attitudes and behavior regarding MMR uptake. Data were extracted using an inductive grounded theory approach. Results: In all, 20 high-quality studies were identified. Vaccine hesitancy or refusal were mainly due to concerns about vaccine safety, effectiveness, perception of measles risk and burden, mistrust in experts, and accessibility. Factors for MMR uptake included a sense of responsibility toward child and community health, peer judgement, trust in experts and vaccine, and measles severity. Anthroposophical and Gypsy, Roma, and Traveler populations presented unique barriers such as accessibility. Conclusion: A multi-interventional, evidence-based approach is vital to improve confidence, competence, and convenience of measles vaccination uptake. Healthcare professionals need an understanding of individual contextual attitudes and barriers to MMR uptake to tailor effective communication. Effective surveillance is needed to identify under-vaccinated populations for vaccination outreach programs to improve accessibility and uptake.